Efficiency of fluralaner pour-on in different strategic control protocols against Rhipicephalus microplus on Brangus cattle in a tropical area - Guilherme Henrique Reckziegel; Mariana Green de Freitas; Juliane Francielle Tutija; Vinícius Duarte Rodrigues; Dyego Gonçalves Lino Borges; Murilo Damasceno Brunet de Freitas; Tiago Gallina; Welber Daniel Zanetti Lopes; Daniel de Castro Rodrigues; Heitor de Oliveira Arriero Amaral; Tom Strydom; Siddhartha Torres; et al. (Parasites & Vectors, 2024)
Abstract Background The occurrence of higher winter temperatures in Brazilian areas with tropical and highland climates may result in a fifth peak of tick populations during winter in addition to the four generations previously described. Therefore, a strategic control protocol was developed with treatments in two seasons with the objective of controlling the generations of ticks that occur in spring/summer and those that occur in autumn/winter. Methods The study was conducted in Mato Grosso do Sul, Brazil, from the beginning of the rainy season, November 2020, to October 2021. In a randomized block design, 36 calves were distributed into three groups: (i) negative control; (ii) traditional strategic control in one season (SC1S), at the beginning of the rainy season; and (iii) strategic control in two seasons (SC2S), at the beginning and end of the rainy season. The SC1S strategic control group was treated on day 0, November 2020, and twice more with intervals of 42 days. The SC2S group received three more treatments beginning on day 182, May 2021, with intervals of 42 days. All treatments consisted of 5% fluralaner (Exzolt® 5%) delivered via a pour-on dose of 1 mL/20 kg body weight. Counts of semi-engorged female ticks were performed on day 3 and every 14 days thereafter, and the animals were weighed at the same time. Results Fluralaner showed a mean efficacy of more than 95% up to day 294. The two treated groups showed a decrease (P < 0.05) in the average number of ticks on day 3. In the SC2S group, the means were close or equal to zero throughout the study, while in the SC1S group, the means did not differ (P > 0.05) from those of the control group from day 231 onward. The final mean weight gain of each group was 76.40 kg, 98.63 kg, and 115.38 kg for the control, SC1S, and SC2S groups, respectively, differing (P < 0.05) from each other. Conclusions Therefore, three applications of fluralaner, with one application every 42 days from the beginning of the rainy season in the middle spring, resulted in effective tick control for 224 days. When three additional treatments were given in autumn/winter with intervals of 42 days between applications, tick counts were reduced throughout the year. This strategic control approach may be indicated in years with climatic conditions that allow that population peaks are expected to occur in the autumn/winter period. Graphical Abstract